Sucroferric oxyhydroxide for the treatment of hyperphosphatemia. (3rd July 2018) - Sprague, Stuart M.; Floege, Jürgen
ABSTRACT: Introduction : Sucroferric oxyhydroxide is a non-calcium, iron-based phosphate binder indicated for the treatment of hyperphosphatemia in patients with chronic kidney disease undergoing dialysis. Areas covered : Herein, the preclinical development and clinical data for sucroferric oxyhydroxide are reviewed, including the key data from the Phase III registration study and the latest evidence from the real-world clinical setting. Expert opinion : Sucroferric oxyhydroxide displays potent phosphate-binding capacity and clinical studies demonstrate its effectiveness for the long-term reduction of serum phosphorus levels in dialysis patients. Observational study data also show that sucroferric oxyhydroxide provides effective serum phosphorus control for hyperphosphatemic patients in the real-world clinical setting. The serum phosphorus reductions with sucroferric oxyhydroxide can be achieved with a relatively low pill burden in comparison with other phosphate binders, which may translate into better treatment adherence in clinical practice. The Phase III data also indicate that sucroferric oxyhydroxide has a favorable impact on other chronic kidney disease-related mineral bone disease parameters, including a fibroblast growth factor-23-lowering effect. Sucroferric oxyhydroxide is well tolerated and associated with low systemic iron absorption, minimizing the potential for iron accumulation or overload. These attributes render sucroferric oxyhydroxide an attractive non-calcium-containing phosphate binder for the treatment of hyperphosphatemia.